Implementation of Goods and Services Procurement Policy in Handling Victims of KDRT at UPTD PPA Sidoarjo Regency, East Java - Fauziah, Luluk; Mashudi, Mashudi; Windriya, Anafil; Abadi, Totok Wahyu; Rahmawati, Irena (Asian Journal of Logistics Management, 2022)
The state is always present in solving problems of violence, including sexual violence against women and children. The presence of this state is also one of the embodiments of the Indonesian constitution which states that the Government of the Republic of Indonesia was formed to protect the entire nation and the entire homeland of Indonesia. Cases of violence against women and children (KtPA) is an iceberg phenomenon. Cases that are recorded and reported are only a small part of the cases that actually occur in the community. Cases of violence against women and children occur both in the family realm (KDRT) and in the public sphere, with a wider spectrum with increasingly diverse modes. The purpose of this study is to describe how the implementation of the Policy on the Procurement of Goods and Services in handling victims of domestic violence, who are the actors associated with the implementation of the Policy on the Procurement of goods and services in the handling of victims and what are the factors constraining the implementation of the Policy on the Procurement of goods and services in the handling of victims of domestic violence in Indonesia. UPTD PPA Sidoarjo Regency, East Java.